Nutritional status assessment among infants under six months exclusively breastfed and non-exclusively breastfed in Jos North LGA, Plateau State, Nigeria - Jacdonmi, Itse; Muhamad Saliluddin, Suhainizam; Ismail, Suriani; Zoakah, Ayuba Ibrahim; Jacdonmi, Gbubemi R. (Association of Medical Researchers, 2016)
Objective: To determine breastfeeding practices and the nutritional status of infants under six months in Jos north LGA, Plateau state, Nigeria Design: A cross-sectional study design was employed. 310 mother-infant pairs were selected as study sample from three primary health care centers in the study location. Data collection consisted of the administration of a validated questionnaire and anthropometric measurements were taken. Results: 39.7 % were seen to practice exclusive breastfeeding while 60.3 practiced non-exclusive breastfeeding. 33 % of infants had already been introduced to complementary foods even before theage of 6 months. In terms of prevalence of malnutrition among males, 13.2 % were severely stunted, 1.6 % were severely underweight and 6.5 % were wasted. Among females, 8.4 % were severely stunted, 0.6 % were severely underweight and 6.6% were severely wasted. There was a significant difference in nutritional indices and breastfeeding patterns (p<0.05). Conclusion: For a decline in malnutrition prevalence, the early introduction of complementary foods by mothers and care givers must be strongly discouraged. Counselling should be targeted at mothers to encourage exclusively breastfeed for 6 months after which appropriate and adequate complementary foods should be introduced.